PMU-based system identification for wide area robust PSS design in interconnected power systems with wind farm - Ngamroo, Issarachai (My University, 2012)
It is well known that the penetration of wind power in the smart power grids not only causes the power fluctuation problem, but also results in the system instability. To tackle this problem, a sophisticated design of robust power system stabilizer (PSS) based on system identification using multiple synchronized phasor measurement units (PMUs) is proposed. The small load fluctuation is applied to the system in order to generate the phasor data measured from multiple PMUs which are assumed to be located in the system. Applying the least square method, the phasor data are used to identify the coupled vibration model (CVM) which represents the dominant inter-area oscillation modes. The CVM is used to design the PSS which is a 2nd-order lead-lag compensator. To take system uncertainties such as variation of system parameters etc., in the CVM, the inverse additive perturbation model is applied. Based on an enhancement of the robust stability margin and damping effect, the PSS parameters optimization problem is formulated. The genetic algorithm is used to solve the problem and achieve the PSS parameters. The performance and robustness of the proposed PSS are evaluated in the IEEJ Western Japan 10 machine power system with wind farm in comparison with a conventional PSS. © 2012 Praise Worthy Prize S.r.l. - All rights reserved.
Keywords: Genetic algorithm; Inter-area oscillation; Phasor measurement unit; Power system stabilizer; Robust control; System identification; Wind farm